Correlation between Oxygen Saturation of patient and Severity Index of Covid 19 Pneumonia on CT - Samreen Mushtaq, Abdul Sattar, Sadia Anjum (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the correlation between capillary blood oxygen saturation and Computerized tomography (CT) severity index in patients with Covid-19 pneumonia. Study design: A cross sectional study design Setting & duration: Ibne-sina hospital Multan Medical & Dental College Multan, from 1st June 2020 to 1st June 2021 Methods: A cross-sectional analytical study was conducted at the COVID-19 ward of Ibne-sina hospital Multan Medical & Dental College Multan for 1 year. At the time of admission, all capillary oxygen saturation of all the included patients was measured. Pulmonary CT scans were then performed on these patients and CT severity index was calculated. SPSS was used for data analysis. Results: A total of 170 Covid-19 infected patients were included in the study. At the time of admission, the mean oxygen saturation was found to be 88.9%±6.53%. Whereas, the mean severity index was15.01±7.79. 22 patients had hypoxia when presented in hospital and a significantly high iCT severity index was found in these patients (p=0.001). Chronic obstructive pulmonary disease (COPD), hypertension, and diabetes were significantly related to reduced blood oxygen saturation (p<0.05). A significant inverse correlation was found between capillary oxygen saturation and CT severity index (r= −0.41, p< 0.01). Conclusions: The study revealed a significant inverse correlation between capillary oxygen saturation and CT severity index. Moreover, it was found that underlying commodities (i.e., past medical history) can also affect the CT severity index.